Explaining Parent-Child Relationship During The Covid-19 Pandemic in Semarang City - Agustin Erna Fatmasari; Niken Fatimah Nurhayati (Islamic Psychology Department, Dakwah Faculty of Universitas Islam Tribakti Lirboyo Kediri, 2023)
The relationship with parents is one source of happiness and psychological well-being for children. The impact of the relationship is undoubtedly essential for children in dealing with rapid changes, such as the COVID-19 pandemic. This study aims to explain the parent-child relationship during the COVID-19 pandemic in Semarang. The method used in this study is indigenous psychology with a grounded theory approach. The data retrieval technique used is purposive sampling by filling out the open-ended questionnaire. A total of 207 emerging adult children aged 17-23 suitable for the inclusion criteria were willing to participate in this study. The study found that the parent-child relationship was getting closer during the COVID-19 pandemic in Semarang for respondents who were close before the pandemic. However, there has been no change in parents and children who have a distant relationship since before the pandemic. This study also indicates that communication, giving support, father’s character, togetherness, loving, and thinking of fathers as role models are forms of the father-child relationship. Moreover, the forms with their mothers are indicated by the communication, loving, togetherness, mother’s character, and giving support.